CITRA KEMISKINAN DAN WATAK TOKOH DALAM CERITA PENDEK “ORANG KAMPUNG” KARYA JONI ARIADINATA TINJAUAN SOSIOLOGI SASTRA DAN RELEVANSINYA PADA PEMBELAJARAN BAHASA - Anis fitria; Moh. Ahsan Shohifur Rizal (Institute Agama Islam Al-Qolam Malang, 2021)
In the short story by Joni Ariadinata has an image of poverty and the character of the characters in it. In addition, the image of poverty and the character of the senidri figure has several types which will be discussed in this study. This study entitled